Magnesium oxide as an effective catalyst in catalytic wet oxidation of H2S to sulfur - Lee, EK; Jung, KD; Joo, OS; Shul, YG (SPRINGER, 2004)
Four different magnesium oxides were studied in the wet oxidation of H'S to sulfur. The H2S removal capacity of MgO in the catalytic wet oxidation strongly depends on the pore size distribution. The MgO with relatively large pores (>100 Angstrom) showed a high removal capacity of H2S. It is suggested that the large pore size favors H2S removal in the catalytic wet oxidation due to the limitation of diffusion.
Keywords: HYDROGEN-SULFIDE; SURFACE-PROPERTIES